LUNG CANCER: Radiological Characteristics with Multislice Computed Tomography Imaging (MSCT) - سرحيل, رفيق (Latakia University Journal -Medical Sciences Series, 2021)
Background and objectives: CT has an important role in detecting primary bronchial carcinoma and differentiating it from other focal pulmonary lesions, in addition to its importance in detecting secondary metastasis, staging the tumor, and investigating tumor recurrence after treatment. Lung cancer is a common cause of death worldwide, so early and accurate diagnosis contributes to early and appropriate treatment. Subjects and Methods: This was an analytic study, included 57 patients (79% male, 21% female) in Tishreen University Hospital, Latakia, Syria. Patients underwent Multidetector Computed Tomography MDCT scan and comparison with pathology results. Results: We found soft tissue mass (88%), speculated heterogeneous mass with heterogeneous enhancement (45%), without calcifications in all cases. We detect cavitations in 18%, pleural tail in 29%, curvilinear opacity that extends toward the ipsilateral hilum (11%), and toward both pleura and hilum in 16%. The accuracy of MDCT was 96% compared to pathology.